Article RETRACTED due to manipulation by the authors Relationship between lung vital capacity, nutritional status activity and motivation to exercise on physical fitness among students in Jakarta - Kukuh Wahyudin Pratama; Fahmy Fachrezzy; Marlinda Budiningsih; Masnur Ali; Uzizatun Maslikah; Abdul Alim; Doni Pranata; Abdul Saman; Octavian Arianto; Panggung Sutapa; Deni Hardianto; Agus Kristiyanto; et al. (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This research aims to determine the vital capacity of the lungs, nutritional status, physical activity and motivation to exercise on physical fitness for students of Jakarta 140 Junior High School in 2019, a sample of 60 male and female students. This research uses a survey method to see the effect between variables. Data analysis techniques using path analysis. Path analysis technique is used to test the direct and indirect effects on vital lung capacity, nutritional status, physical activity and motivation to exercise on physical fitness in students of Jakarta 140 Junior High School. Path analysis technique with the help of SPSS program version 20.00 at the significance level α = 0.05. The results of this research are as follows: (1) The vital capacity of the lungs directly influences physical fitness; (2) Nutritional status directly influences physical fitness; (3) Physical activity directly influences physical fitness; (4) Sport motivation has a direct effect on physical fitness; (5) the vital capacity of the lungs directly affects the motivation to exercise; (6) Nutritional status directly influences sports motivation; (7) Physical activity directly influences the motivation to exercise; (8) Lung's vital capacity through motivation to exercise simultaneously has direct effect on physical fitness; (9) Nutritional status through motivation to exercise simultaneously has direct effect on physical fitness; and (10) Physical activity through motivation to exercise simultaneously has direct effect on physical fitness. Thus, the higher the lung's vital capacity, nutritional status, physical activity and motivation to exercise a person, the better the physical fitness level of the person and vice versa, the lower the vital capacity of the lungs, nutritional status, physical activity, then the lower the person's physical fitness level.